All in the mind: understanding the social economy enterprise innovation in Spain. Issue 5 (29th July 2014) - Padilla-Meléndez, Antonio; Rosa Del Aguila-Obra, Ana; Lockett, Nigel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Several studies have investigated the factors affecting innovation in medium-sized enterprises (SMEs) at different levels. However, research into the characteristics of the entrepreneur (individual level) in social economy enterprises (SEE), and the relationship to innovation is scarce. The purpose of this paper is to build upon previous innovation literature to analyse SEE innovativeness. Design/methodology/approach – This paper empirically analyses data from 193 face-to-face interviews with the founder/owner/managing director of small (zero to nine employees) SEE in Andalucía, Spain. A semi-structured questionnaire was produced using the literature review. To ensure the reliability of the data collection and the consistency of the results, several researchers reviewed the codification and analysis of the answers. Quantitative analyses were performed on the data, including descriptive statistical analysis and multivariate analysis (factorial for innovativeness construct validation, multiple regression, cluster, and discriminant). The software SPSS IBM PASSW Statistics 18 was used. Findings – Considering the individual factors, it was determined that a proactive attitude towards innovation and a degree-level education were positively related to SEE innovativeness and that these were the most significant factors considered. The identification of attitude towards innovation was perhaps not surprising; one might expect a relationship between proactiveness and innovativeness. Furthermore, this result is consistent with the positive impact exerted by entrepreneurial characteristics, such as entrepreneurial confidence and adaptability, or SME entrepreneurs' proactive personality and prospector strategy orientation towards their firms' innovation. Research limitations/implications – This study has a number of limitations. First, the study is an exploratory study of innovativeness in SEE in a limited geographical area. Second, the fact that the interviews were conducted using a semi-structured questionnaire limited the opportunities for obtaining more detailed information regarding the factors affecting innovativeness in SEE. Third, other variables may have been used as control variables, such as firm age. Sector was used as control variable and it was found as not significant. Fourth, other statistical analyses, such as hierarchical linear modelling, would benefit the results, as different levels of analysis would be considered simultaneously. Fifth, other components of entrepreneurial orientation would render the results more complete. Practical implications – The research findings suggest that SEE would benefit from degree-level people with proactive attitudes towards innovation. Clearly, attitude and education are important aspects of the individual's mindset. This study demonstrates that the mind sets of the owners of SEE, in terms of both education and attitude, positively impact innovativeness. At least in SEE, degree-level entrepreneurs with positive attitudes towards innovation run more innovative firms. The challenge for regional policy makers is to look beyond the formal education system to promote innovation skills programmes for social and economic impact. Originality/value – This paper contributes to the entrepreneurship and innovation literature by identifying the importance of developing individual-level skills as well as formal education in order to foster innovation in SEEs.